1989
DOI: 10.3109/00365528909090789
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-gliadin Antibody Profile in Childhood Protracted Diarrhoea Due to Coeliac Disease and Other Causes in a Developing Country

Abstract: Serum anti-gliadin antibody (AGA) titres were estimated by diffusion in a gel enzyme-linked immunosorbent assay in children with coeliac disease (n = 11), protracted diarrhoea of non-coeliac causes (n = 110), acute gastroenteritis (n = 20), protein energy malnutrition (n = 20), and asymptomatic, well-nourished children (n = 66). The mean IgG and IgA AGA titres were significantly higher (p less than 0.001) in children with coeliac disease than in any other groups. There was no significant difference (p greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
15
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…However, until the 1950s it was not known (6,7,17), where wheat is a staple food. In all of these series, diagnosis of CD was established on the basis of villous atrophy on intestinal mucosal biopsy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, until the 1950s it was not known (6,7,17), where wheat is a staple food. In all of these series, diagnosis of CD was established on the basis of villous atrophy on intestinal mucosal biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are sporadic reports of CD from Arabia (1)(2)(3) and India (4)(5)(6)(7). Celiac disease was reported from India in 1966 (4), and subsequently Nelson et al (8) reported a series of 17 immigrant Asian children with CD from Birmingham.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Khoshoo et al (30), in India, reported that IgG and IgA antigliadin antibodies were significantly higher in children with celiac disease than in children with other enteropathies.…”
Section: Discussionmentioning
confidence: 99%